Influence of Polyethylene and Oxidized Polyethylene Wax Emulsions on Leaching Dynamics of Boric Acid from Impregnated Spruce Wood - Boštjan Lesar; Polonca Kralj; Miha Humar (Drvna Industrija, 2010)
Boron biocides belong to the most frequently used ingredients of commercial wood preservatives. They are very effective fungicides and insecticides, but they do not react with wood and thus leach from it in wet applications. This fact signifi cantly limits use of boron compounds in the field of wood preservation. In order to reduce leaching of boric acid, the emulsion of polyethylene (WE1) and an emulsion of oxidized polyethylene (WE6) wax were combined with boric acid (cB = 0.1 % or 0.5 % of boron). Spruce wood specimens were vacuum impregnated and afterwards leached according to the prCEN/TS 15119-1, EN 1250-2 and EN 84 procedures. The results showed that the boron leaching is predominantly infl uenced by moisture content of wood during leaching, and furthermore by the concentration gradient (frequency of water replacement). The fact that the prCEN/TS 15119-1 leaching procedure is less severe than other two methods is also refl ected in the results. The results of the EN 84 and ENV 1250 test are comparable, while the results of the prCEN/TS 15119-1 testing are not in line with the other two methods. Considerable portions of boron are leached from wood in the first leaching cycles, already. WE6 wax emulsion (oxidized polyethylene wax emulsion) in combination with heat treatment reduces boron leaching to a certain extent. On the other hand, impregnation of wood with WE1 (polyethylene wax emulsion) does not reduce it and it even enhances it.